Selection of human immunodeficiency virus type 1 R5 variants with augmented replicative capacity and reduced sensitivity to entry inhibitors during severe immunodeficiency - Repits, Johanna; Öberg, Monica; Esbjörnsson, Joakim; Medstrand, Patrik; Karlsson, Anders; Albert, Jan; Fenyö, Eva Maria; Jansson, Marianne (Journal of General Virology, 2005)
Early in human immunodeficiency virus 1 (HIV-1) infection CCR5-using (R5) viruses predominate. With disease progression, approximately 50 % of infected individuals develop viruses able to use CXCR4. In the present work, the evolution of the biological properties of HIV-1 was studied in patients who retain viruses with an R5 phenotype despite AIDS onset. A panel of primary R5 HIV-1 isolates sequentially obtained at an asymptomatic stage and after AIDS diagnosis was examined. The viruses were selected based on our previous observation that R5 variants with reduced sensitivity to RANTES inhibition may appear during disease progression. Biological properties of the early and late R5 viruses, including infectivity, replicative capacity, impact of cationic polymer and sensitivity to inhibition by the entry inhibitors T-20 and TAK-779, were evaluated. R5 viruses isolated after AIDS onset displayed elevated replicative capacity and infectivity, and did not benefit from cationic polymer assistance during infection. Late R5 isolates also exhibited reduced sensitivity to inhibition by T-20 and TAK-779, even though the included patients were naïve to treatment with entry inhibitors and the isolates had not acquired mutations within the gp41 HR1 region. In addition, CD4+ T-cell counts at the time of R5 virus isolation correlated with infectivity, replicative capacity and sensitivity to inhibition by entry inhibitors. The results indicate that R5 HIV-1 variants with augmented replicative capacity and reduced sensitivity to entry inhibitors may be selected for during severe immunodeficiency. At a time when the clinical use of entry inhibitors is increasing, this observation could be of importance in the optimal design of such treatments.